Scientists' warning to humanity on illegal or unsustainable wildlife trade. (November 2021) - Cardoso, Pedro; Amponsah-Mensah, Kofi; Barreiros, João P.; Bouhuys, Jamie; Cheung, Hubert; Davies, Alisa; Kumschick, Sabrina; Longhorn, Stuart J.; Martínez-Muñoz, Carlos A.; Morcatty, Thais Q.; Peters, Gretchen; Ripple, William J.; et al.
Abstract: Illegal or unsustainable wildlife trade is growing at a global level, threatening the traded species and coexisting biota, and promoting the spread of invasive species. From the loss of ecosystem services to diseases transmitted from wildlife to humans, or connections with major organized crime networks and disruption of local to global economies, its ramifications are pervading our daily lives and perniciously affecting our well-being. Here we build on the manifesto 'World Scientists' Warning to Humanity, issued by the Alliance of World Scientists. As a group of researchers deeply concerned about the consequences of illegal or unsustainable wildlife trade, we review and highlight how these can negatively impact species, ecosystems, and society. We appeal for urgent action to close key knowledge gaps and regulate wildlife trade more stringently. Highlights: Illegal or unsustainable wildlife trade threatens numerous species. Both targeted and non-targeted species are affected by wildlife trade. Invasive species and the loss of ecosystem services exacerbate problems. Disease transmission to humans is currently a major concern. Criminal networks and effects on local and global economies are pervasive.